Pengaruh Harga dan Nilai TukarTerhadap Volume Ekspor Ikan Tuna di Provinsi Sulawesi Selatan Tahun 2003-2017 - Fauzia F Alamri; Fitriani Latief; Ridwan Ridwan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to: (a) find out that the exchange rate and price have a partially positive and significant effect on the volume of tuna exports in South Sulawesi. (b) find out that the exchange rate and price have a simultaneous positive and significant effect on the volume of tuna exports in South Sulawesi. This study used multiple linear regression with secondary data collection. The result of this study showed that simultaneously,the price and exchange rate variables. Significantly and positively affected toward the volume of tuna exports in South Sulawesi. Partially the price had a significant effect toward the volume of tuna exports in South Sulawesi and the exchange rate also had a significant effect toward the volume of tuna exports in South Sulawesi.